Characterization of multiplication commutative rings with finitely many minimal prime ideals. Issue 11 (2nd November 2019) - Alsuraiheed, T.; Bavula, V. V.
Abstract: The aim of the article is to give a characterization of a multiplication commutative ring with finitely many minimal prime ideals: Each such ring is a finite direct product of rings ∏ i = 1 n D i where Di is either a Dedekind domain or an Artinian, local, principal ideal ring and vice versa . In particular, each such ring is a Noetherian ring. As a corollary subclasses of such rings are described (semiprime, Artinian, semiprime and Artinian, local, domain, etc.).